Analysis of Dynamic Archive Management to Support Public Services at Tawangrejo Village Office - Yuli Astuti, Anis; Nukha Murtadlo, Muhamad (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study explores dynamic archive management at the Tawangrejo Village Office, Tunjungan District, Blora Regency, to improve public service efficiency. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation. Findings show that archive workflows follow procedures but are limited by manual recording, lack of duplication, and no electronic tracking. Storage is disorganized due to the absence of a dedicated archive room, SOPs, and trained staff documents are often stacked randomly or left in corners. Maintenance is minimal, with no scheduled checks, leading to damage from pests. Moreover, the village lacks an official Records Retention Schedule, weakening proper archive retention. Major challenges include insufficient human resources, infrastructure, and training. It is recommended that the village establish SOPs, create a retention schedule, train staff regularly, appoint archive personnel, and provide appropriate storage. These steps can strengthen transparency, accountability, and service effectiveness in the village administration.